Evaluating the individual, situational, and technological drivers for creative ideas generation in virtual communities: A systematic literature review - Zhao, Xin; Wang, Chunzhen; Hong, Jianzhong (Frontiers in Psychology, 2022)
The setting in which people generate ideas and work collaboratively to solve problems is gradually shifting from traditional face-to-face communities to virtual communities. Virtual communities are, therefore, becoming a new source of creative ideas. Nevertheless, online creativity is not without challenges. The main obstacle seems to be a lack of active engagement from participants within these virtual communities, resulting in a low quality and quantity of creative content when compared to traditional methods of creation. Research suggests that successfully generating creative ideas online involves sustained, active engagement among collaborators. A number of studies have investigated various factors related to the generation of creative ideas within virtual communities. However, a comprehensive understanding of contributing factors remains elusive. This study examines past research on the factors that drive creative ideas generation in online creative communities through a systematic literature review. The study seeks to analyse research findings over the past decade and provide an overview of the main driving factors, research areas, research trends, and implications for future research. Web of Science and Scopus were used to identify relevant articles, while Google Scholar was used to minimise the risk of missing any valuable data related to the aim of this study. The results provide an overview of the studies examining creative ideas generation within virtual communities. By approaching the subject matter from three primary perspectives (individual, situational, and technological), this paper identifies influencing factors associated with the successful generation of creative ideas online. The results of the paper also provide an overview of the research methods and guiding theories adopted by current researchers. The paper concludes with research trends and recommendations for future research.